Gender & Breeding Postdoctoral Fellow Initiative - McDougall, Cynthia (WorldFish, 2018)
Presented by Cynthia McDougall (WorldFish), as part of the Annual Gender Capacity Development Workshop hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 27-28 September 2018.